Fibrous Agricultural Biomass as a Potential Source for Bioconversion to Vanillic Acid - Pei-Ling Tang; Osman Hassan; Jamaliah Md-Jahim; Wan Aida Wan Mustapha; Mohamad Yusof Maskat (International Journal of Polymer Science)
This study was conducted to assess the potential of six fibrous agricultural residues, namely, oil palm empty fruit bunch fiber (OPEFBF), coconut coir fiber (CCF), pineapple peel (PP), pineapple crown leaves (PCL), kenaf bast fiber (KBF), and kenaf core fiber (KCF), as a source of ferulic acid and phenolic compounds for bioconversion into vanillic acid. The raw samples were pretreated with organosolv (NaOH-glycerol) and alkaline treatment (NaOH), to produce phenol-rich black liquor. The finding showed that the highest amount of phenolic compounds and ferulic acid was produced from CCF and PP, respectively. This study also found that organosolv treatment was the superior method for phenolic compound extraction, whereas alkaline treatment was the selective method for lignin extraction. Vanillic acid production by Aspergillus niger I-1472 was only observed when the fermentation broth was fed with liquors from PP and PCL, possibly due to the higher levels of ferulic acid in those samples.